First, add #color(red)(10)# to each side of the equation to put the equation in standard form:
#x^2 - 3x + color(red)(10) = -10 + color(red)(10)#
#x^2 - 3x + 10 = 0#
We can use the quadratic equation to solve this problem:
The quadratic formula states:
For #color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0#, the values of #x# which are the solutions to the equation are given by:
#x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))#
Substituting:
#color(red)(1)# for #color(red)(a)#
#color(blue)(-3)# for #color(blue)(b)#
#color(green)(10)# for #color(green)(c)# gives:
#x = (-color(blue)(-3) +- sqrt(color(blue)(-3)^2 - (4 * color(red)(1) * color(green)(10))))/(2 * color(red)(1))#
#x = (3 +- sqrt(9 - 40))/2#
#x = (3 +- sqrt(-31))/2#